2000
DOI: 10.1007/bf03401940
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of Angiotensin I-Converting Enzyme as a Candidate Gene Involved In Exudative Inflammatory Resistance in F344/N Rats

Abstract: genic and pro-inflammatory stimuli (1-5). LEW/N and F344/N rats respectively, are susceptible and relatively resistant to a broad range of inflammatory/autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The reciprocal nature of tissue Ace and Ac-SDKP levels in susceptible tissues of Fischer and Lewis strains may explain the moderation of end organ damage in the latter strain. Using the N-terminally specific tetrapeptide substrate, both Ace activity and catalytic properties have been reported to be identical in both Lewis and Fischer strains (48). …”
Section: Discussionmentioning
confidence: 99%
“…The reciprocal nature of tissue Ace and Ac-SDKP levels in susceptible tissues of Fischer and Lewis strains may explain the moderation of end organ damage in the latter strain. Using the N-terminally specific tetrapeptide substrate, both Ace activity and catalytic properties have been reported to be identical in both Lewis and Fischer strains (48). …”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of the coding regions of these genes in the parental strains used in this intercross indicated no difference between LEW/N and F344/N rats in the CRHR1, and a point mutation in ACE resulting in a leucine to phenylalanine switch near the N-terminal active site of the enzyme (Jafarian-Tehrani et al 2000). Further analysis revealed that while the non-specific activity of ACE was elevated in the strain that showed the mutation (F344/N rats), there was no difference between the two strains in specific activity of the enzyme, and treatment of the rats with ACE inhibitors did not affect the inflammatory phenotype.…”
Section: Genetics Of Autoimmune/inflammatory Disease Susceptibilitymentioning
confidence: 94%
“…There is good evidence in the mammalian circulation that HA is metabolically stable. The tripeptides hippuryl-L-histidyl-L-leucine (van Platerink et al, 2007) and hippurylglycylglycine (Jafarian-Tehrani et al, 2000) are commonly employed as substrates for angiotensin converting enzyme (ACE; peptidyl-dipeptidase A; EC 3.4.15.1) and are hydrolyzed by dipeptidase activity leaving the stable HA. Circulating HAwill certainly be exposed to ACE since it is expressed mainly in lung, vascular endothelium and kidney (Femia et al, 2008).…”
Section: The Glycine Deportation Systemmentioning
confidence: 99%